Effects of carprofen and/or CIDR administration on pregnancies per artificial insemination around pregnancy recognition in lactating dairy cows - ABAY, M; PANCARCI, SM; GUNGOR, O; NAK, Y; ALPARSLAN, AD; BEKYUREK, T (Journal of the Hellenic Veterinary Medical Society, 2021)
Effect of carprofen and/or CIDR on pregnancies per AI (P/AI) 14 days after artificial insemination (AI) in lactating cows were investigated. Following detection of corpus luteum (CL) by ultrasonography (USG) 14 days after AI, cows (n=853) were randomly allocated to CARP (carprofen, 1.4 mg/kg; Rimadyl®XL), CIDR (progesterone, 1.38g, for seven days), CARP+CIDR and CONT (control) groups. CL was re-determined with USG 21 days after AI to monitored the maintenance of CL. Rates of maintenance of CL did not differed among CARP (79.6% [168/211]), CIDR (86.0% [196/228]), CARP+CIDR (80.0% [172/215]) and CONT (74.9% [149/199]) groups; however, the interaction effect of treatment by body condition score (BCS) at AI (P<0.05) were existed. In this matter, among cows with BCS≤2.5, chances of maintenance of CL was lower in CONT (70.7%, [111/157]) group compared to those in CARP (81.7%, [125/153]), CIDR (83.6%, [153/183]) and CARP+CIDR (80.1%, [129/161]) groups. Whereas, among cows with BCS>2.5, chances of maintenance of CL were lower in CARP (74.1%, [43/58]) and CARP+CIDR (79.6%, [43/54]) groups compared to those in CONT (90.5%, [38/42]) and CIDR (95.6%, [43/45]) groups. For the P/AI at 28-32 days after AI, there was no difference among CARP (48.8% [103/211]), CIDR (50.9 [116/228]), CARP+CIDR (47.4% [102/215]) and CONT (44.7% [89/199]) groups. Pregnancy losses between 28-32 and 55-60 days did not differ among CARP (3.9%, [4/103]), CIDR (4.3%, [5/116]), CARP+CIDR (5.9%, [6/102]) and CONT (6.7%, [6/89]) groups. However, there was a significant (P<0.05) interaction effect of treatment by the number of services on pregnancy losses. In this regard, pregnancy losses were higher in cows inseminated thrice and four or more times in CONT (11.8% and 16.7%) group compared to those in CARP (0% and 4.8%), CIDR (0% and 6.9%), CARP+CIDR (0% and 11.1%); respectively. Consequently, no effects of carprofen or CIDR around pregnancy recognition on P/AI were observed despite a higher maintenance rate of CL in lactating cattle. Furthermore, fewer pregnancy losses in cows following three or more services could indicate the beneficial carry-over effects of carprofen and/or CIDR administration around maternal recognition of pregnancy.